2008
DOI: 10.1051/limn:2008010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vegetation cover on the biological traits of pond invertebrate communities

Abstract: Without human intervention, ponds progressively fill up with aquatic vegetation, so that the structure and age of the vegetal formations show great contrasts within a given set of water bodies. We hypothesized that the biological traits of pond invertebrate communities differed significantly among ponds having different vegetal formations. To test this hypothesis, we selected three neighbouring ponds showing a gradient of vegetation cover and type (sparse bryophytes on rocky substrata (pond 1), extensive subme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In an extensive review in North American wetlands, Wissinger (1999) observed that CPOM shredders were rare and so nutrients and energy from detrital resources must enter food webs via FPOM collectors and algal/biofilm grazers. According to Céréghino et al (2008), during the senescence period, aquatic plants at ponds are a source of food for several organisms supplying CPOM and supporting periphyton communities. Annual plants might also produce abundant fast-decaying detritus that should support dense populations of grazers and FPOM collectors, especially chironomids (in our study the functional group of collector-gatherers: JOURNAL OF NATURAL HISTORY 15 Paratanytarsus sp., Paratrichocladius sp.…”
Section: Community Functional Patternsmentioning
confidence: 99%
“…In an extensive review in North American wetlands, Wissinger (1999) observed that CPOM shredders were rare and so nutrients and energy from detrital resources must enter food webs via FPOM collectors and algal/biofilm grazers. According to Céréghino et al (2008), during the senescence period, aquatic plants at ponds are a source of food for several organisms supplying CPOM and supporting periphyton communities. Annual plants might also produce abundant fast-decaying detritus that should support dense populations of grazers and FPOM collectors, especially chironomids (in our study the functional group of collector-gatherers: JOURNAL OF NATURAL HISTORY 15 Paratanytarsus sp., Paratrichocladius sp.…”
Section: Community Functional Patternsmentioning
confidence: 99%
“…These data generally deal with the phenological sequences (Bazzanti et al, 1996, Culioli et al, 2006, differences between temporary and permanent ponds (Bazzanti and Della Bella, 2004), relationships with wet phase duration (Gascon et al, 2008) and vegetation cover (Cé ré ghino et al, 2008), and distributional organization in mesohabitats (Bazzanti et al, 2009).…”
Section: Functional Group-microhabitat Associationsmentioning
confidence: 99%
“…Previous studies have reported several factors that influenced benthic macroinvertebrate communities. These studies suggested that variability in physical factors (e.g., water depth, grain size, habitat complexity and wind exposure) (Sauter and Gu¨de, 1996;Shostell and Williams, 2007;Bazzanti et al, 2009), chemical factors (e.g., nutrients in water and sediment, dissolved oxygen and pH) (Free et al, 2009), and biological factors (e.g., fish predation, macrophytes) (Ce´re´ghino et al, 2008) significantly affect the benthic community.…”
Section: Introductionmentioning
confidence: 99%